Entrepreneurship and Nursing: integrative review - Colichi, Rosana Maria Barreto [UNESP]; Silva e Lima, Stella Godoy [UNESP]; Benito Bonini, Andrea Bueno [UNESP]; Molina Lima, Silvana Andrea [UNESP] (Assoc Brasileira Enfermagem, 2019)
Objective: To identify the knowledge produced on business entrepreneurship in Nursing. Method: Integrative literature review in the following databases: Cumulative Index to Nursing and Allied Health Literature (CINAHL), EMBASE, SCOPUS, Web of Science, PubMed, Medline, Latin American and Caribbean Literature in Health Sciences (LILACS), Nursing Database (BDENF), Index Psychology and National Information Center of Medical Sciences of Cuba (CUMED). We included available studies in their totality in the period from 2007 to 2017. Results: 22 articles were included. The categories that emerged from the study are the following: Concepts of entrepreneurship in nursing, Profile of the entrepreneur nurse, Business Diversity, Business Management, Barriers to business entrepreneurship in nursing, Support to entrepreneurial nurses and Entrepreneurship in Nursing Undergraduate. Conclusion: There is a need to prepare nurses with adequate skills to increase the capacity to integrate into the labor market and to improve their own well-being and that of society.
Keywords: Entrepreneurship; Job Market; Occupational Health; Nursing; Education